Observations on Newcastle disease during routine diagnosis work - Brada, Wilhelm; Silvas, Milton Marques da (Pesquisa Agropecuaria Brasileira, 2014)
The authors report personal observations on Newcastle disease (NCD) and discuss its symptomatology, the isolation of the virus from immunized poultry, failures of vaccination of one-day old chicks and the diagnosis of the disease. The disease was also identified in specimens which presented no symptoms or suggestive pathological alterations. The use of embryonated eggs from bens immunized against NCD, and the inoculation of suspect material in pigeons for diagnosis purposes was also reported. From their observations and experiments, the authors concluded: 1) the immunization of one-day old chicks with attenuated, living virus vaccine did not produce sufficient protection due to an insufficient production of antibodies in the first days of life or in consequence of the presence of material antibodies in the egg-yolk from immunized hens; 2) the virus isolation in diseased hens is possible in spite of the existence, of specific antibodies in its blood; 3) the disease can frequently be diagnosed by H.A. (Hemagglutination) and H.I. (Hemagglutination inhibition) tests in fowls with neither symptomatology nor pathological limb alterations; 4) the use for, diagnostic inoculation, of embryonated eggs from NCD immunized hens caused no damage to the virus culture when embryos were utilized before the starting of the blood circulation that occurs at approximately the 4th day following the incubation. This has proved to be of great value, especially in the differential diagnosis for pasteurellosis and NCD.